ANALISIS PENGARUH FAKTOR PSIKOLOGIS TERHADAP KEPERCAYAAN KONSUMEN E-COMMERCE - Prasetya, Adhitya Yoga (STIE Totalwin Semarang, 2014)
Online trust is one of the main determinants of the success of e-retailers and much research has dealt with website features triggering consumer trust to them. Another stream of research focuses on the psychological antecedents to online trust; i.e., what ââhappensââ in the consumerâs mind before or while a person decides to trust an e-retailer? So far, each effort has focused on only a few selected aspects of this trust formation process. Only few studies have attempted to identify major personality based psychological antecedents of trust. This work identified the relative importance of the personality based psychological antecedents of trust in technology adoption and e-retailing. The model incorporates the personality traits (Extraversion, and Openness to experience), the most widely accepted framework for personality research in psychology, as well as determinants of trust in our model.